2010
DOI: 10.1074/jbc.m109.080614
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Retinoic Acid Receptor-related Orphan Receptor α and γ Activity by 7-Oxygenated Sterol Ligands

Abstract: The retinoic acid receptor-related orphan receptors ␣ and ␥ (ROR␣ (NR1F1) and ROR␥ (NR1F3)) are orphan nuclear receptors and perform critical roles in regulation of development, metabolism, and immune function. Cholesterol and cholesterol sulfate have been suggested to be ROR␣ ligands, but the physiological significance is unclear. To date, no endogenous ROR␥ ligands have been described. Here, we demonstrate that 7-oxygenated sterols function as high affinity ligands for both ROR␣ and ROR␥ by directly binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
187
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(194 citation statements)
references
References 61 publications
6
187
0
Order By: Relevance
“…We provide evidence indicating that some of these genes are regulated directly by ROR␣. Recent studies have suggested that the activity of ROR␣ can be regulated by natural and synthetic compounds (30,55), which raises hopes that ROR␣ may provide a novel therapeutic target in the management and prevention of obesity and related pathologies, such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide evidence indicating that some of these genes are regulated directly by ROR␣. Recent studies have suggested that the activity of ROR␣ can be regulated by natural and synthetic compounds (30,55), which raises hopes that ROR␣ may provide a novel therapeutic target in the management and prevention of obesity and related pathologies, such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that RORs function as ligand-dependent transcription factors (20,23,30,48,55). RORs have been implicated in the regulation of a wide variety of physiological processes, including cerebellar development, metabolism, circadian rhythm, cellular immunity, bone formation, hypoxia signaling, and inflammatory responses (4, 9, 11, 12, 16, 19, 20, 24, 29, 31-33, 42, 43, 47, 49, 54, 58, 60).…”
mentioning
confidence: 99%
“…The basic RORC variant (RORg) is expressed ubiquitously and plays an important function in the regulation of development and metabolism (5). Recently, the 7-oxygenated sterol was identified as an endogenous ligand modulating the function of this transcription factor (6). The expression of RORgT (also termed RORC2) has a very restricted pattern, and its product is predominantly found in immune organs, such as thymus, and in particular lineages of immune cells, such as immature doublepositive thymocytes and Th17 lymphocytes (2,7), where this transcription factor plays important functions in the maturation of a/b T cells and the differentiation of Th17 cells, respectively (2,8).…”
mentioning
confidence: 99%
“…The ligand binding pocket of ROR␣ contains cholesterol or cholesterol sulfate, which may be endogenous ROR␣ ligands (23,24). A recent study shows that 7␣-oxygenated cholesterols are high affinity ligands for ROR␣ and ROR␥ and that 7␣-hydroxycholesterol (7␣-OHC), a product of CYP7A1, is an inverse agonist of ROR␣ that decreases ROR␣ transcriptional activation of gluconeogenic genes to reduce hepatic glucose output (25). This could be a mechanism linking bile acid synthesis to inhibit gluconeogenesis.…”
mentioning
confidence: 99%